The Roots of Scientific System of Pedagogy in Lithuania - Montvilaitė, Sigita (Acta Paedagogica Vilnensia, 2004)
In order to disclose the process of development of Lithuanian pedagogic works of the first half of 20th century towards scientific education discipline and its maturity, this article presents the examples of scientific research of a separate educational problems. In order to strict systematically expressed views on problems of education, there are analysed M. Mačernis, A. Šerkšnas, A. Gučas, A. Maceina pedagogic writings. Special emphasis is put on the book of J. Laužikas – by one of the top Lithuanian educationalists – in which the problem of schoolchildren's self-administration is dealt with for the first time on theoretical and practical levels. The theoretical works of these educationalists are important to the Lithuanian education science by them integral and systematic features. They show that a certain part of Lithuanian authors who analysed problems of education had based them on certain methodological principles and adhered to scientific criteria.
Keywords: history of education; educational science; scientific system; pedagogy; self-administration